2015
DOI: 10.1123/jsep.2014-0199
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Meeting Vigorous Physical Activity Recommendations and Burnout Symptoms Among Adolescents: An Exploratory Study With Vocational Students

Abstract: This study examines how students who met the current recommendations for vigorous physical activity (VPA) of the American College of Sports Medicine (ACSM) and the Centers of Disease Control and Prevention (CDC) differ from peers who did not reach these standards with regard to self-reported burnout, before and after controlling for light physical activity and moderate physical activity. A sample of 144 vocational students (Mage =16.2 years, SD = 1.13, 98 males) completed the International Physical Activity Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 60 publications
3
15
0
Order By: Relevance
“…Further, future studies could also investigate how various levels of physical activity intensity on the bikes (from light to vigorous) may affect students' ability to remain on-task and retain academic material. Elliot et al (2015) examined the effects of various physical activity levels and how they were associated with school burnout in a secondary vocational school.…”
Section: Discussionmentioning
confidence: 99%
“…Further, future studies could also investigate how various levels of physical activity intensity on the bikes (from light to vigorous) may affect students' ability to remain on-task and retain academic material. Elliot et al (2015) examined the effects of various physical activity levels and how they were associated with school burnout in a secondary vocational school.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, from a clinical perspective, we have shown that it is possible to perform aerobic exercise at a moderate-vigorous intensity in this patient group. Vigorous physical activity and high cardiorespiratory fitness has been shown to have an important role in improving mental health [ 41 ], burnout [ 42 ] and cardio-metabolic risk factors, especially for individuals with high levels of perceived stress [ 43 ]. In this study, individual PAP was one of the components in the MMR, with recommendations to perform physical activity of moderate to high intensity.…”
Section: Discussionmentioning
confidence: 99%
“…We did not find any baseline differences in clinically relevant insomnia symptoms between athletes who completed the follow-up (11%) and those who dropped out from T1 to T2 (10%). Our findings reveal that compared to adolescents attending normal school classes (7%), clinically relevant burnout levels were more prevalent in our sample if the same definition and cut-offs are used to estimate burnout (Elliot et al, 2015). This highlights that stress is an important issue among young elite athletes, and that specific measures are needed for this specific target population to either make their lives less stressful or to promote personal and social resources that enable them to more successfully cope with stress.…”
Section: Discussionmentioning
confidence: 66%